Stress–Strain Model of High-Strength Concrete Confined by Lateral Ties under Axial Compression - Lei Wang; Xiaokun Huang; Fuquan Xu (Buildings, 2023)
High-strength concrete can effectively reduce the cross-sectional size, increase space usage, and cut material costs. To analyze the mechanical properties of high-strength concrete vertical members, various confinement models have been proposed to define the ties-confined concrete stress–strain relationship. However, most existing models are divided into ascending and descending segments. These are continuous but not derivable at the peak point, which does not facilitate numerical calculations. Moreover, these models have a large number of parameters that are mostly obtained based on the fitting of experimental data, which may also lead to the limited applicability of the models. In this study, existing confinement models for high-strength concrete under axial compression are reviewed, and the differences between the models are discussed. Based on the results of normal triaxial experiments on high-strength concrete and the test data from other studies on ties-confined concrete columns, the effective confinement coefficient and empirical formula of ties strain at the peak stress of confined concrete are proposed. A confinement model is proposed based on the continuous derivable function, and it is validated based on the available experimental data. Results show that the proposed model can reflect the stress–strain relationship of the test specimens more simply while keeping the basic accuracy with other models.